Tear Proteomics of Children and Young Adult Soft Contact Lens, Orthokeratology and Spectacle Wearers – A Pilot Study. (3rd June 2022) - Chao, Cecilia; Lattery, Lauren; Qin, Guoting; Kamat, Manasi; Basso, Kari; Lakkis, Carol; Hasan, Mohamad; Richdale, Kathryn
Abstract: Purpose: Contact lens complications occur more often in older teenagers and young adults compared to children. This study explored differences in tear proteomics between children and young adults wearing soft contact lens (SCL), orthokeratology or spectacles for >3 years. Methods: Twelve children and 12 sex- and correction-matched young adults were enrolled. Tears were collected via Schirmer strips for tear proteomic analysis using mass spectrometry. Proteome Discoverer was used for protein identification. Label-Free Quantitation was generated using Scaffold software; Fisher's Exact tests were used to compare proteins by age and correction groups. Generalized linear models were used to assess differences in overall protein levels by age and correction groups. A secondary analysis of proteins presented in >50% of samples of each group was conducted using the R/Bioconductor limma package. Results: There were 385 proteins present only in young adults while 183 were unique in children. There were 528 unique proteins to SCL, 96 to orthokeratology and 149 to spectacle wearers. Based on Fisher's Exact analyses, 126 proteins were higher in young adults than children (all P  < 0.048). Forty-seven protein levels were higher in SCL compared to orthokeratology (all P  < 0.01), 33 protein levels were higher in SCL compared to spectacles (all P  < 0.01), 15 protein levels were higher in orthokeratology compared to spectacle wearers (all P  < 0.01). Based on generalized linear models, young adults had higher overall protein levels than children ( P  = 0.001), SCL had higher protein levels than spectacle wearers ( P  < 0.001) but no differences were found between orthokeratology and spectacle wearers ( P  = 0.79). Based on the secondary analysis, only Antileukoproteinase was higher in the young adult orthokeratology group compared to other groups ( P  < 0.01). Conclusions: Tear protein type and abundance differ by age and correction. Further research is needed to understand the effects of contact lens correction in children and young adults on the tear proteome.